2020
DOI: 10.21608/eos.2020.42567.1002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of shear bond strength of brackets bonded with four different bonding protocols at different time intervals; An in vitro study

Abstract: Objective: To test shear bond strength and mode of debonding of brackets bonded using a traditional orthodontic adhesive (Transbond XT), self-adhesive material (Heliosit) and selfetch &self-adhesive resin material (Vertise flow) with and without phosphoric acid etching; after 15 minutes, 24 hours and following aging and thermocycling. Materials and Methods: One hundred and eighty upper first premolar teeth were used in this study. The specimens were equally and randomly allocated into four groups. TXT group (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
1
0
0
Order By: Relevance
“…However, it has been established that Heliosit’s bond strengths for orthodontic bonding fall within the recommended range for clinical use. 28 – 31 The current study found it less invasive on the teeth, similar to Transbond XT. This was evident from the evenly distributed adhesive remnant index scores between ARI scores of “1” and “2”.…”
Section: Discussionsupporting
confidence: 61%
“…However, it has been established that Heliosit’s bond strengths for orthodontic bonding fall within the recommended range for clinical use. 28 – 31 The current study found it less invasive on the teeth, similar to Transbond XT. This was evident from the evenly distributed adhesive remnant index scores between ARI scores of “1” and “2”.…”
Section: Discussionsupporting
confidence: 61%